Preparation method of high-purity alpha-Al2O3 granulation powder

By mixing components such as α-Al2O3, magnesium oxide and calcium oxide in a specific proportion and particle size, high-purity α-Al2O3 granulation powder is solved, and the high-purity ceramic granulation powder is expensive and insufficient volume resistivity is insufficient. It has achieved the improvement of the density and strength of ceramics, which are suitable for large-scale production and high-precision applications.

CN119118169APending Publication Date: 2024-12-13浙江富乐德半导体材料科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411209679.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing high-purity α-Al2O3 granulated powder mainly relies on imported supply, is expensive and unstable in supply, and the volume resistivity of high-density alumina ceramics on the market is insufficient, which cannot meet the needs of high-precision engineering.

Method used

By mixing components such as α-Al2O3, magnesium oxide and calcium oxide in a specific proportion and particle size, high-purity α-Al2O3 granulation powder is prepared through spray granulation process, adding dispersants, binders and lubricants to improve ceramics volume resistivity and density.

Benefits of technology

It has achieved the improvement of the volume resistivity of ceramics, ensured the density and strength of the material, reduced production costs, was suitable for large-scale production, and met a wider application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118169A_ABST
    Figure CN119118169A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional ceramics, and discloses a preparation method of high-purity alpha-Al2O3 granulated powder, which comprises the following steps: uniformly mixing high-purity alpha-Al2O3 with magnesium oxide, calcium oxide and other additives according to weight components, sieving, deironing, filtering, standing, defoaming, granulating, and removing impurities to obtain the high-purity alpha-Al2O3 granulated powder. The preparation method is simple in process and low in cost, large-scale production can be achieved, the cost is reduced, meanwhile, the volume resistivity of the aluminum oxide ceramic is effectively improved by adding calcium oxide and magnesium oxide, and meanwhile the compactness and strength of the material can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional ceramics, and mainly to a method for preparing high-purity alpha-Al2O3 granulated powder. Background Art

[0002] High-purity alumina ceramics not only have the advantages of high insulation, high thermal insulation, corrosion resistance, and high hardness, but also have a wide source and low price cost. It is currently one of the world's largest produced and most widely used ceramic materials, and is widely used in semiconductors, mechanical processing, chemical industry, aerospace and other fields.

[0003] Alumina has many isomorphous crystals, such as α-Al2O3, β-Al2O3, γ-Al2O3, etc. Among them, α-Al2O3 has the highest stability, compact crystal structure, stable physical and chemical properties, high density and mechanical strength, and is widely used in industry. High-purity alumina ceramics are ceramic materials with an Al2O3 content of more than 99.9%. Due to its sintering temperature of up to 1650-1990°C, it has good insulation properties and can be used as integrated circuit substrates and high-frequency insulation materials in the semiconductor industry.

[0004] High-density alumina ceramics are mostly formed by pressing, which is an important forming method in the production of advanced ceramics. As its production requires increasingly fine raw materials, in order to improve the fluidity of the powder, improve the sintering performance, and reduce the sintering temperature, the alumina powder needs to be made into pseudo-granules, that is, granulated powder, so as to evenly fill the model to increase the molding density of the green body and ensure the sintering density after ceramic formation. Therefore, in the production process of alumina ceramic products, granulation is the basis and one of the most important links. At present, domestic high-purity α-Al2O3 granulated powder is mainly imported from Japan and France, with high prices, and is easily affected by international trade rules, and the supply channels are unstable. At the same time, the volume resistivity of high-density alumina ceramics on the market is low, which cannot meet some applications in high-precision engineering and cannot meet a wider range of needs. Summary of the invention

[0005] In order to improve the fluidity of powder, enhance sintering performance, reduce sintering temperature, and reduce the price of high-purity granulated powder, large-scale production can be achieved to meet a wider range of usage needs. The present invention provides a preparation method of high-purity α-Al2O3 granulated powder, which has a simple process, low cost, and can be produced on a large scale. Calcium oxide is added to the original process to improve the volume resistivity of high-density alumina ceramics, and magnesium oxide is added to ensure the density and strength of the material.

[0006] The technical solution of the method for preparing high-purity α-Al2O3 granulated powder of the present invention comprises the following steps: a) weighing α-Al2O3, magnesium oxide, calcium oxide, a dispersant, a binder, a surfactant, a lubricant and a solvent according to the components, and mixing them uniformly to obtain a slurry, wherein the particle size of α-Al2O3 is 0.5-2 μm, the particle size of magnesium oxide is 0.5-1 μm, the particle size of calcium oxide is 1.5-2.5 μm, and the mass ratio of calcium oxide to α-Al2O3 is 99.0-99.5:0.1-0.4; b) screening, deironing, filtering, standing and defoaming the slurry, and then granulating to obtain a crude product; c) The crude product is sieved and iron removed to obtain the product.

[0007] In this technical solution, magnesium oxide plays an important role in the fine-grained microstructure of alumina ceramics. Magnesium oxide can maintain the amount of liquid phase in the sintering system during sintering, and a small amount of second-phase crystals such as spinel and aluminate are generated. In addition, the particle size of α-Al2O3 is 0.5-2μm, and the particle size of magnesium oxide is 0.5-1μm. The particle size of magnesium oxide is less than or equal to that of α-Al2O3, which makes magnesium oxide have a pinning effect on grain boundary movement, and they effectively inhibit the growth of grains. The team of the present invention accidentally discovered during the experiment that the introduction of calcium oxide into the above system can significantly increase the volume resistivity of ceramics. The reason for this is that the Ca contained in calcium oxide 2+ The larger radius and stronger valence bond can effectively block the migration of other ions, thereby improving the volume resistivity of the ceramic. The present invention further found that the amount of calcium oxide and its particle size have a significant local effect on the volume resistivity of the ceramic. Finally, the present invention found that the improvement effect is most significant when the mass ratio of calcium oxide to α-Al2O3 is 99.0-99.5:0.1-0.4 and the particle size is 1.5-2.5μm.

[0008] Preferably, α-Al2O3 is in powder form with a purity of >99.9%.

[0009] Preferably, the magnesium oxide is in powder form with a purity of >99.9%.

[0010] Preferably, the calcium oxide is in powder form with a purity of >99.9%.

[0011] Preferably, in step a), each component is weighed using an automated system.

[0012] As a preference, when mixing uniformly in step a), an automatic circulating ball mill is used for ball milling. Preferably, the ball milling time of the automatic circulation ball mill is 10 to 30 hours.

[0013] Furthermore, the components in the slurry in step a) are calculated by weight as follows: 99.0 to 99.5 parts of α-Al2O3, 0.1 to 0.5 parts of magnesium oxide, 0.075 to 0.4 parts of calcium oxide, 0.2 to 1.5 parts of dispersant, 3 to 5 parts of binder, 0.1 to 2 parts of surfactant, 1 to 8 parts of lubricant, and 20 to 30 parts of solvent.

[0014] Furthermore, the dispersant in step a) is one or more of polyacrylamide and ammonium polyacrylate.

[0015] Furthermore, the binder in step a) is one or more of polyvinyl alcohol, methyl cellulose and ethyl cellulose.

[0016] Furthermore, the surfactant in step a) is one or more of lauric acid, stearic acid and palmitic acid.

[0017] Furthermore, the lubricant in step a) is one or more of stearic acid and poly-α-olefin.

[0018] Furthermore, the viscosity of the lubricant is 50 to 70 mm 2 / S.

[0019] Furthermore, the solvent in step a) is RO water.

[0020] Furthermore, the pH of RO water is 6-7, and the conductivity is ≤2us / cm.

[0021] Furthermore, the granulation method in step b) is spray granulation.

[0022] Preferably, the granulation is carried out in a granulation tower, and the parameters of the granulation tower are: the inlet air temperature is 150-230°C, the exhaust air temperature is 50-120°C, and the atomizer speed is 3000-12000rpm.

[0023] The beneficial effects of this technical solution are:

[0024] 1. Doping magnesium oxide and calcium oxide during the granulation process can effectively increase the volume resistivity of alumina ceramics while ensuring the density and strength of the material.

[0025] 2. The particle size of α-Al2O3, magnesium oxide and calcium oxide is small, and the powder activity is high, which is conducive to the sintering and densification of the powder.

[0026] 3. Additives such as dispersants, binders, surfactants and lubricants have low costs and improve economic benefits.

[0027] 4. The preparation process is simple, fully automated, and highly efficient and energy-saving. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a picture of the granulated powder sample prepared in Example 1 of the present invention.

[0029] Figure 2 This is the particle size distribution diagram of the granulated powder sample prepared in Example 1 of the present invention.

[0030] Figure 3 The strength test results of the granulated powder test block prepared in Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below by way of examples. All raw materials used in the examples are commercially available or can be prepared by conventional methods.

[0032] Among them, the pH value of RO water = 7, and the conductivity ≤ 2us / cm.

[0033] The purity of α-Al2O3 powder is 99.93%, the purity of magnesium oxide powder is 99.93%, and the purity of calcium oxide powder is 99.93%.

[0034] Example 1

[0035] (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0036] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0037] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0038] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0039] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0040] (5) Impurities removal The crude product obtained in step (4) is subjected to iron removal and sieving to obtain granulated powder. The obtained granulated powder sample is as follows: Figure 1 As shown, the sample particle size distribution diagram of the granulated powder obtained is as follows Figure 2 shown.

[0041] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) were tested, wherein the test temperature for the volume resistivity test was 25°C and the test humidity was 50%, the test temperature for the density test was 25°C, and the test results for the bending strength were as follows: Figure 3 shown.

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that in step (2), the average particle size of the added magnesium oxide is 0.2 μm, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0044] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0045] Specifically, the average particle size of magnesium oxide is 0.2 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0046] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0047] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0048] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0049] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that in step (2), the average particle size of the added magnesium oxide is 3 μm, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve four parts of methylcellulose, one part of polyacrylamide, and two parts of stearic acid in 20 parts of RO water.

[0052] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0053] Specifically, the average particle size of magnesium oxide is 3 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0054] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0055] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0056] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0057] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0058] Table 1 is a comparative data of the effect of magnesium oxide particle size on the performance of the test block of granulated powder From the data in Table 1, we can clearly see that if the magnesium oxide particle size is too large or too small, the density and bending strength of the test block of the granulated powder will decrease, but it will have little effect on the volume resistivity of the granulated powder.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that in step (2), magnesium oxide is not added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0061] (2) Mixing Add 0.2 parts of calcium oxide to the solution obtained in step (1), premix for 20 minutes until the powder is evenly dispersed in the solution, then continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0062] Specifically, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0063] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0064] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0065] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0066] (6) Detection performance The density, volume resistivity and bending strength of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0067] Comparative Example 4

[0068] The difference between this comparative example and Example 1 is that in step (2), 0.1 parts of magnesium oxide is added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0069] (2) Mixing Add 0.1 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0070] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0071] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0072] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0073] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0074] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0075] Comparative Example 5

[0076] The difference between this comparative example and Example 1 is that in step (2), 1 part of magnesium oxide is added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0077] (2) Mixing Add 1 part of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0078] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0079] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0080] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0081] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0082] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0083] Table 2 Comparative data on the effect of magnesium oxide addition on the performance of granulated powder It can be seen from the final test performance data in Table 2 that the addition amount of magnesium oxide has a great influence on the density and bending strength of the granulated powder, but has little effect on the volume resistivity of the granulated powder. Compared with the data in Table 1, it can be seen that the addition amount of magnesium oxide has a greater impact on the performance of the granulated powder than the particle size of magnesium oxide.

[0084] Comparative Example 6

[0085] The difference between this comparative example and Example 1 is that in step (2), the average particle size of the added calcium oxide is 0.8 μm, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0086] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0087] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 0.8 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0088] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0089] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0090] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0091] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0092] Comparative Example 7

[0093] The difference between this comparative example and Example 1 is that in step (2), the average particle size of the added calcium oxide is 5 μm, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0094] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0095] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 5 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0096] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0097] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0098] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0099] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0100] Table 3 is a comparative data of the effect of calcium oxide particle size on the performance of the test block of granulated powder According to the data in Table 3, it can be obtained that if the particle size of calcium oxide is too large or too small, the volume resistivity of the test block of the final granulated powder will be reduced, but it has almost no effect on the density and bending strength of the test block of the granulated powder.

[0101] Comparative Example 8

[0102] The difference between this comparative example and Example 1 is that in step (2), no calcium oxide is added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0103] (2) Mixing Add 0.4 parts of magnesium oxide to the solution obtained in step (1), premix for 20 minutes until the powder is evenly dispersed in the solution, then continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0104] Specifically, the average particle size of the oxidase is 3 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0105] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0106] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0107] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0108] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0109] Comparative Example 9

[0110] The difference between this comparative example and Example 1 is that in step (2), 0.08 parts of calcium oxide is added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0111] (2) Mixing Add 0.1 parts of magnesium oxide and 0.08 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0112] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0113] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0114] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0115] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0116] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0117] Comparative Example 10

[0118] The difference between this comparative example and Example 1 is that in step (2), 1 part of calcium oxide is added, and the rest of the process is the same as that of Example 1. The specific process is as follows: (1) Dissolution Dissolve 4 parts of methylcellulose, 1 part of polyacrylamide, and 2 parts of stearic acid in 20 parts of RO water, where the viscosity of stearic acid is 55 mm 2 / s.

[0119] (2) Mixing Add 0.1 parts of magnesium oxide and 0.08 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0120] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0121] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0122] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 200°C, exhaust air temperature 100°C, and atomizer speed 8000rpm.

[0123] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0124] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) are tested, wherein the test temperature for the volume resistivity test is 25° C., the test humidity is 50%, and the test temperature for the density test is 25° C.

[0125] Table 4 Comparative data on the effect of calcium oxide addition on the performance of the test blocks of granulated powder It can be seen from the final test performance data in Table 4 that the amount of calcium oxide added has a great influence on the volume resistivity of the test block of the granulated powder, but has little effect on the density and bending strength of the granulated powder. Compared with the data in Table 1, it can be seen that the effect of the amount of calcium oxide added on the performance of the granulated powder is greater than the effect of the particle size of calcium oxide.

[0126] Example 2

[0127] (1) Dissolution Dissolve 3 parts of ethyl cellulose, 1 part of polyacrylamide, 1 part of stearic acid and 1 part of palmitic acid in 30 parts of RO water, where the viscosity of stearic acid is 60 mm 2 / s.

[0128] (2) Mixing Add 0.4 parts of magnesium oxide and 0.2 parts of calcium oxide to the solution obtained in step (1), and premix for 20 minutes until the powder is evenly dispersed in the solution. Then, continue to add 99.4 parts of α-Al2O3 powder to the solution, continue stirring and premixing for 30 minutes until the powder is evenly dispersed, to obtain a slurry with a solid content of 55% and good fluidity.

[0129] Specifically, the average particle size of magnesium oxide is 0.5 μm, the average particle size of calcium oxide is 2 μm, and the average particle size of α-Al 2 O 3 is 1 μm.

[0130] (3) Defoaming The slurry obtained in step (2) is treated in a slurry treatment system and allowed to stand to remove bubbles.

[0131] (4) Spray granulation The slurry obtained in step (3) is sprayed and granulated to obtain a crude product. The parameters of the granulation tower are: inlet air temperature 160°C, exhaust air temperature 50°C, and atomizer speed 12000 rpm.

[0132] (5) Impurities removal The crude product obtained in step (4) is deironed and sieved to obtain granulated powder.

[0133] (6) Detection performance The density, volume resistivity and bending strength of the test block of the granulated powder obtained in step (5) were tested, wherein the test temperature for the volume resistivity test was 25°C and the test humidity was 50%, and the test temperature for the density test was 25°C; the bending strength test temperature was 25°C, and the measured density was 3.953 g / cm 3 , the volume resistivity is 5.37*10 16 Ω·cm, and the bending strength is 466Mpa.

[0134] The above description is a preferred implementation case of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high purity α-Al 2 O 3 Method for preparing granulated powder, Its characteristics are: The following steps are involved: a) α-Al 2 O 3 , magnesium oxide, calcium oxide, dispersant, binder, surfactant, lubricant and solvent are mixed evenly to obtain slurry, wherein α-Al 2 O 3 The particle size of magnesium oxide is 0.5~2μm, the particle size of calcium oxide is 0.5~1μm, the particle size of calcium oxide is 1.5~2.5μm, and the particle size of calcium oxide and α-Al 2 O 3 The mass ratio is 99.0~99.5:0.1~0.4; b) sieving, removing iron, filtering, standing and defoaming the slurry, and granulating to obtain a crude product; c) Screen the crude product to remove iron and obtain high-purity α-Al 2 O 3 Granulating powder.

2. A high-purity α-Al according to claim 1 2 O 3 Method for preparing granulated powder, Its characteristics are: The components in the slurry in step a) are calculated by weight: α-Al 2 O 3 99.0~99.5, 0.1~0.4 parts of magnesium oxide, Calcium oxide 0.1~0.4 parts, Dispersant 0.2~1.5 parts, 3~5 parts of adhesive, Surfactant 0.1~2 parts, 1~8 parts of lubricant, 20~30 parts of solvent.

3. A high-purity α-Al according to claim 1 or 2 2 O 3 Method for preparing granulated powder, Its characteristics are: The dispersant described in step a) is one or more of polyacrylamide and ammonium polyacrylate.

4. A high-purity α-Al according to claim 1 or 2 2 O 3 Method for preparing granulated powder, Its characteristics are: The binder in step a) is one or more of polyvinyl alcohol, methyl cellulose and ethyl cellulose.

5. A high-purity α-Al according to claim 1 2 O 3 Method for preparing granulated powder, Its characteristics are: The surfactant described in step a) is one or more of lauric acid, stearic acid and palmitic acid.

6. A high-purity α-Al according to claim 1 2 O 3 Method for preparing granulated powder, Its characteristics are: The lubricant in step a) is one or more of stearic acid and poly-α-olefin.

7. A high-purity α-Al according to claim 6 2 O 3 Method for preparing granulated powder, Its characteristics are: The viscosity of the lubricant is 50~70mm 2 / S.

8. The high-purity α-Al according to claim 1 2 O 3 Method for preparing granulated powder, Its characteristics are: The solvent in step a) is RO water.

9. A high-purity α-Al according to claim 8 2 O 3 Method for preparing granulated powder, Its characteristics are: The RO water pH=6~7, conductivity ≤2us / cm.

10. The high-purity α-Al according to claim 1 2 O 3 Method for preparing granulated powder, Its characteristics are: The granulation method in step b) is spray granulation.

Citation Information

Cited By

  • Rare-earth-doped high-density alumina ultrahigh-voltage insulating ceramic as well as preparation method and application thereof

    CN120647347A